A new species of Dolicholana Bruce, 1986 (Isopoda, Cymothoidea, Cirolanidae), the first record of the genus from the Atlantic Ocean - Paiva, Ricardo J. C.; Souza-Filho, Jesser F. (Zootaxa, 2015)
The isopod genus Dolicholana Bruce, 1986, previously known only from the Indo-West Pacific, is recorded for the first time from the Atlantic Ocean. A new species, Dolicholana brucei sp. nov., is described from the northeastern Brazilian coast, and is the first record of the genus Dolicholana Bruce, 1986 for the Atlantic Ocean. The material was collected from the upper part of the continental slope off Rio Grande do Norte (150 m depth). The new species is characterized by pereopod 1 propodal palm being crenulate, ischium of pereopod 1 and 2 with a plumose seta on the anterior margin, peduncle of pleopods 3–5 bearing an accessory lobe acute on the distolateral angle, pleotelson posterior margin being rounded, and the uropodal endopod and the exopod apices distally being rounded. A revised key to the genus is provided.